The immediate post-operative period following lung transplantation: mapping of nursing interventions - Rayssa Thompson Duarte; Graciele Fernanda da Costa Linch; Rita Catalina Aquino Caregnato (Universidade de São Paulo, 2014)
OBJECTIVES: to investigate the principle nursing interventions/actions, prescribed in the immediate post-operative period for patients who receive lung transplantation, recorded in the medical records, and to map these using the Nursing Interventions Classification (NIC) taxonomy.METHOD: retrospective documental research using 183 medical records of patients who received lung transplantation (2007/2012). The data of the patients' profile were grouped in accordance with the variables investigated, and submitted to descriptive analysis. The nursing interventions prescribed were analyzed using the method of cross-mapping with the related interventions in the NIC. Medical records which did not contain nursing prescriptions were excluded.RESULTS: the majority of the patients were male, with medical diagnoses of pulmonary fibrosis, and underwent lung transplantation from a deceased donor. A total of 26 most frequently-cited interventions/actions were found. The majority (91.6%) were in the complex and basic physiological domains of the NIC. It was not possible to map two actions prescribed by the nurses.CONCLUSIONS: it was identified that the main prescriptions contained general care for the postoperative period of major surgery, rather than prescriptions individualized to the patient in the postoperative period following lung transplantation. Care measures related to pain were underestimated in the prescriptions. The mapping with the taxonomy can contribute to the elaboration of the care plan and to the use of computerized systems in this complex mode of therapy.